1987
DOI: 10.1021/jm00384a017
|View full text |Cite
|
Sign up to set email alerts
|

Substituted arylmethyl phenyl ethers. 1. A novel series of 5-lipoxygenase inhibitors and leukotriene antagonists

Abstract: A series of new substituted arylmethyl phenyl ethers has been prepared. These compounds were tested as inhibitors of 5-lipoxygenase (5-LO) in rat neutrophils, in vitro antagonists of leukotriene-induced contraction of guinea pig (GP) lung parenchymal strips, and inhibitors of slow reacting substance of anaphylaxis (SRS-A) mediated bronchospasm in the GP in vivo. Most representatives of this new class of potential antiallergic/antiinflammatory agents showed potent inhibition of 5-LO activity in rat PMNs. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 1 publication
(2 reference statements)
0
30
0
Order By: Relevance
“…We therefore concluded that LTs are involved in the Ca 2ϩ -dependent acidification in RAW 264.7 macrophages. In this context, the inhibitory effect of REV 5901, a potent inhibitor of 5-lipoxygenase (Musser et al, 1987) as well as a competitive antagonist of peptide LTs , on UTPinduced acidification (Table 1) also supports this notion. These findings provide a novel downstream mechanism for AA-induced intracellular acidification.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…We therefore concluded that LTs are involved in the Ca 2ϩ -dependent acidification in RAW 264.7 macrophages. In this context, the inhibitory effect of REV 5901, a potent inhibitor of 5-lipoxygenase (Musser et al, 1987) as well as a competitive antagonist of peptide LTs , on UTPinduced acidification (Table 1) also supports this notion. These findings provide a novel downstream mechanism for AA-induced intracellular acidification.…”
mentioning
confidence: 60%
“…AA-induced intracellular acidosis also was abolished by pretreatment with MK-886 (10 M) plus baicalein (10 M) (three experiments, data not shown). REV 5901, a 5-lipoxygenase inhibitor (Musser et al, 1987) as well as a competitive antagonist of peptide LTs (Musser et al, 1987), also markedly attenuated the UTP response (Table 1). All the drugs tested had no cytotoxic effects on RAW 264.7 cells as determined by MTT assays (data not shown).…”
Section: Utp-induced Extracellular Camentioning
confidence: 96%
“…We also studied the role of the LOX pathway on 3T6 fibroblast proliferation with LT receptor antagonists. We used U-75302, REV-5901, and LY-171883 as LTB 4 , LTD 4 , and CysLT receptor antagonists, respectively (28)(29)(30). All antagonists induced a low growth and […”
Section: Effect Of Lox Inhibitors and Lt Receptor Antagonists On The mentioning
confidence: 99%
“…[42] Diethyl (2-Cyanobenzyl)phosphonate (20), [43] Diethyl (3-Cyanobenzyl)phosphonate (21), [44] and Diethyl (4-Cyanobenzyl)phosphonate (23) [45] : These compounds were prepared from the commercially available chloromethyl benzonitriles and triethyl phosphite according to the procedures given above.…”
Section: Diethyl [4-(hexyloxy)benzyl]phosphonate (19)mentioning
confidence: 99%